Creation of a Vivaldi-Based Circular Antenna Array for Broadband Relay Channels - Pavel A. Mezhevov; Konstantin O. Korovin; Aleksey N. Likontsev (Известия высших учебных заведений России: Радиоэлектроника, 2023)
Introduction. Unmanned aerial vehicles (UAVs) are rapidly gaining in popularity. The UVA development requires active antenna systems capable of forming a narrow beam of the main lobe of the radiation pattern. Although numerous studies have considered specialized antenna arrays with a wide range of scanning angles, the location of such systems on UAVs remains under-investigated. The development of such arrays for UAVs will enable the creation of a secure relay broadband channel with a few repeaters.Aim. Development of a broadband antenna array for UAVs with the possibility of setting the main lobe of the radiation pattern in any direction of the azimuthal plane, for use in relay tasks.Materials and methods. An emitter model and a circular antenna array on its basis was developed in the Ansys HFSS electromagnetic modeling package.Results. The dependence of the directional coefficient and the gain for an array consisting of 8 and 16 elements was shown. Voltage standing-wave ratio dependences and directivity patterns that satisfy the conditions of retransmission in a wide-frequency band using UAVs were obtained. Recommendations on the number of active elements in a circular antenna array that ensure the maximum gain (directivity) were formulated.Conclusion. Technical solutions that can be used in the development of UAVs are proposed. The system can be further improved by optimizing the antenna array elements and using a cylindrical or hemispherical array.